2022
DOI: 10.14218/jcth.2022.00204
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease in Lean/Nonobese and Obese Individuals: A Comprehensive Review on Prevalence, Pathogenesis, Clinical Outcomes, and Treatment

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most com

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 171 publications
0
12
0
1
Order By: Relevance
“…This contrasted with results in lean NAFLD patients, where the FLI emerged as a more reliable marker for hepatic steatosis with a cutoff value of >16.5, while WHtR performed suboptimally. This discrepancy highlights the complexity of diagnosing NAFLD and the potential need for different diagnostic criteria based on body composition (19,20). Interestingly, the percentage of fatty liver in the lean population was higher than typically seen in Western populations.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasted with results in lean NAFLD patients, where the FLI emerged as a more reliable marker for hepatic steatosis with a cutoff value of >16.5, while WHtR performed suboptimally. This discrepancy highlights the complexity of diagnosing NAFLD and the potential need for different diagnostic criteria based on body composition (19,20). Interestingly, the percentage of fatty liver in the lean population was higher than typically seen in Western populations.…”
Section: Discussionmentioning
confidence: 99%
“…(ii) Diet is an important factor in NAFLD. Studies have found that lean individuals tend to consume more fructose and cholesterol, which will promote the occurrence of NAFLD [ 43 , 44 ]. (iii) Other factors such as metabolic syndrome, disrupted gut microbiota, and decreased skeletal muscle mass and function have also been implicated in the formation of non-obese NAFLD [ 42 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to obesity-induced insulin resistance's primary function in promoting hepatic steatosis, MASLD is the most common hepatic manifestation of Metabolic Syndrome (MetS) [4,7,[11][12][13][14]. MetS comprises a group of metabolic abnormalities associated with an increased risk of insulin resistance and cardiovascular disease (CVD).…”
Section: Introductionmentioning
confidence: 99%